2012
DOI: 10.1073/pnas.1113788109
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in coyotes (Canis latrans) in response to the megafaunal extinctions

Abstract: Living coyotes modify their behavior in the presence of larger carnivores, such as wolves. However, little is known about the effects of competitor presence or absence on morphological change in coyotes or wolves over long periods of time. We examined the evolution of coyotes and wolves through time from the late Pleistocene, during which many large carnivorous species coexisted as predators and competitors, to the Recent; this allowed us to investigate evolutionary changes in these species in response to clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 65 publications
9
51
1
Order By: Relevance
“…These weights are similar to the estimated mass of Ice age Coyotes during the Pleistocene era, believed to be "super-sized" compared to modern Coyotes (Meachen and Samuels 2012). Chambers (2010) asserted that previous researchers (e.g., Bossert 1969, 1975) measuring canid morphometics grouped northeastern Coyotes with other populations of Coyotes and hence they should continue to be called Coyotes.…”
Section: Morphologysupporting
confidence: 50%
“…These weights are similar to the estimated mass of Ice age Coyotes during the Pleistocene era, believed to be "super-sized" compared to modern Coyotes (Meachen and Samuels 2012). Chambers (2010) asserted that previous researchers (e.g., Bossert 1969, 1975) measuring canid morphometics grouped northeastern Coyotes with other populations of Coyotes and hence they should continue to be called Coyotes.…”
Section: Morphologysupporting
confidence: 50%
“…Such a scenario may be perceived as unlikely, because it would require major, convergent body size reductions over only several thousand years. However, recent nonhuman studies have shown that body size may undergo substantial evolutionary change in relatively short timeframes (56,57). The case of rainforest hunter-gatherers could be a similar human example of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Carnivore community composition can also impact carnivore morphology; the presence of other carnivores can drive dental character displacement in a range of species (Dayan, 1992;Dayan and Simberloff, 1998). Recent work by Meachen and Samuels (2012) documents this effect at La Brea, finding stasis in C. lupus but change in C. latrans across the Pleistocene/Holocene transition. Detailed geometric morphometric analysis of shape and size change across the carnivore guild at La Brea has yet to be attempted.…”
Section: Previous Researchmentioning
confidence: 96%